2003
DOI: 10.1021/jp026056s
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Solvent Coordination Effects on Titanium-Based Epoxidation Catalysts. Part One:  Formation of the Titanium Hydroperoxo Intermediate

Abstract: Density functional theory has been used to study the effects of solvent coordination on the structure and formation of the titanium hydroperoxo species believed to be the active intermediate in oxidation reactions with Ti(IV)−H2O2 catalytic systems. Titanium hydroperoxo intermediates possessing a variety of coordination environments have been modeled with unconstrained single coordination sphere clusters using a B3LYP/ECP methodology. Titanium hydroperoxo intermediates bearing one or two solvent ligands may as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 56 publications
(115 reference statements)
9
114
3
Order By: Relevance
“…All attempts to obtain a TiOO-H side-on coordination structure were, however, unsuccessful because the optimization always evolved towards geometries with a g 1 -coordination. This result contrasts with the recent B3LYP study of Sever and Root on the Ti(OH) 3 OOH model clusters who found structures with a g 2 -coordination for the OOH group [92]. This dissimilarity may be due to the different coordination number of titanium in the Ti-POM and Ti(OH) 3 OOH as well as due to the different basicity of Ti-O-W and Ti-O-H bonds.…”
Section: Dft Calculationscontrasting
confidence: 85%
See 1 more Smart Citation
“…All attempts to obtain a TiOO-H side-on coordination structure were, however, unsuccessful because the optimization always evolved towards geometries with a g 1 -coordination. This result contrasts with the recent B3LYP study of Sever and Root on the Ti(OH) 3 OOH model clusters who found structures with a g 2 -coordination for the OOH group [92]. This dissimilarity may be due to the different coordination number of titanium in the Ti-POM and Ti(OH) 3 OOH as well as due to the different basicity of Ti-O-W and Ti-O-H bonds.…”
Section: Dft Calculationscontrasting
confidence: 85%
“…For successful designing new catalysts and processes, we needed a basic knowledge about the mechanism of the formation of active titanium species and the mechanisms of their interaction with organic substrates. Although considerable efforts, both theoretical and experimental, have been directed to understanding activity observed in TS-1 and related materials [9,[66][67][68][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94], much remained to be realised regarding the nature of the active oxidising species and chemical interactions at the molecular level. This stimulated our interest to model mechanistic studies on the titanium-single-site-catalysed oxidations.…”
Section: Introductionmentioning
confidence: 99%
“…40 Other oxidation products including DFF and HMFCA were also detected, and believed to be the intermediates. 40 Other oxidation products including DFF and HMFCA were also detected, and believed to be the intermediates.…”
Section: Catalytic Oxidation Of Hmf Into Fdca With T-buooh In Variousmentioning
confidence: 99%
“…36 The aerobic oxidation of HMF over γ-Fe 2 O 3 @-HAP-Pd(0) catalyst was therefore initially carried out in a range of solvents in order to assess the effect of the solvent. Table 1 shows the results of aerobic oxidation of HMF in each solvent, the dielectric constant of the solvent being indicated.…”
Section: Aerobic Oxidation Of Hmf In Various Solventsmentioning
confidence: 99%